Transformasi Pendidikan: Meningkatkan Kualitas Belajar Melalui Pelatihan Penggunaan AI bagi Guru SDN 1 Jambangan - Abror, Haikal; Cahya Anggraen, Lenita (Universitas Negeri Semarang, 2025)
The rapid advancement of technology today ensures that every individual can adapt to utilizing it. One technology that can be utilized in learning is artificial intelligence. Artificial intelligence has the potential to change practices in aspects of life, especially in the aspect of education. The purpose of this community service is to improve the skills and knowledge of teachers in utilizing artificial intelligence for learning purposes. The target is teachers of Elementary School 1 Jambangan. The methods used are socialization and training. The stages of activity include preparation and planning, implementation, and evaluation. The training process, which includes an introduction to artificial intelligence such as Chat GPT and Bard, is carried out intensively. Next is the direct practice session. The results show a significant increase in teachers' ability to use Chat GPT and Bard with a participant satisfaction rate of up to 96%. Teachers can compile materials and browse materials that are in accordance with learning needs. With the ease of browsing materials, the learning objectives that have been set can be achieved.